PSYCHOLOGICAL AND PHYSIOLOGICAL CHARACTERISTICS OF EARLY ADOLESCENCE - Isakhanova Mokhidil Erkinovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the development of the motivational sphere of the individual during early adolescence, the stage of maturity, physiological, psychological and social limits, and information about the acceleration processes.